Human services management : organizational leadership in social work practice - Austin, David M. (Foundations of social work knowledge., 2012)
Human services management occurs in nonprofit, governmental, and for-profit sectors and involves a wide variety of organizational structures. These diverse conditions shape the effort to produce and project services that directly affect the quality of life of individuals, families, and communities through social welfare, health and mental health, criminal justice, and educational services. David Austin begins with an examination of the historical development and distinctive characteristics of human service organizations, the variety of organizational and program structures at play, and the con.